Pancreatic Insufficiency is Not a Prevalent Problem in Alagille Syndrome - Kamath, Binita M. (2012)
Alagille syndrome (ALGS) is an inherited multisystem disorder in which pancreatic insufficiency has been regarded a minor but important clinical manifestation. As part of a multi-center prospective study, 42 ALGS patients underwent fecal elastase (FE) measurement to screen for exocrine pancreatic insufficiency (PI). FE measurements were normal (>200 μg/g) in 40 (95%) and indeterminate (100-200 μg/g) in 2 (5%). Since FE is the most reliable screen for PI, these data suggest that PI is not a prevalent problem in ALGS.